Narrowing of attention following food cue exposure in emerging adults: Does impulsivity matter?. (1st April 2017) - Fields, Sherecce A.; Smallman, Rachel; Hicks, Joshua A.; Lange, Krista; Thamotharan, Sneha
Abstract: Obesity has reached epidemic proportions over the past few decades and research is beginning to focus on the behavioral and cognitive mechanisms that may contribute to the rise of obesity in youth and emerging adults. Based on previous models of obesity and current research on the activation of approach motivational states, we predicted that impulsive individuals and individuals with high body dissatisfaction would demonstrate a narrowing of attentional focus in response to food-cue exposure. Participants ( n  = 101) completed a task assessing attentional breadth in response to food and non-food cues, followed by measures of eating behaviors and delay discounting (a measure of impulsive decision making). The findings revealed that delay discounting and the interaction between BMI and body dissatisfaction predicted narrowing of attentional scope following the presentation of food cues. Implications for how these findings might account for the link between impulsivity, body dissatisfaction and maladaptive eating are discussed. Highlights: Delay discounting predicted narrowing of attentional scope after food cues. The Interaction between body dissatisfaction and BMI was related to attentional scope. The preference for immediate reward may be related to attentional scope.